2014
DOI: 10.1590/s1415-47572014005000002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and haplotypes of the organic cation transporter 1 gene (SLC22A1) in the Xhosa population of South Africa

Abstract: Human organic cation transporter 1 is primarily expressed in hepatocytes and mediates the electrogenic transport of various endogenous and exogenous compounds, including clinically important drugs. Genetic polymorphisms in the gene coding for human organic cation transporter 1, SLC22A1, are increasingly being recognized as a possible mechanism explaining the variable response to clinical drugs, which are substrates for this transporter. The genotypic and allelic distributions of 19 nonsynonymous and one intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…14 To address this issue, the reduced function methionine deletion at codon 420 (Met420del) variant of SLC22A1 (rs72552763) was selected for this study since its allele frequency is higher in Ethiopian population as compared to other African population. [23][24][25] Furthermore, Met420del is the most studied functional variant of SLC22A1 gene for its influence on metformin pharmacokinetics though there were inconsistent reports based an extensive survey of recent literature. In addition, this variant is generally observed in combination with a rare loss of function polymorphism, Cys88Arg (rs55918055), that causes improper membrane localization of OCT1, resulting in metformin gastrointestinal intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…14 To address this issue, the reduced function methionine deletion at codon 420 (Met420del) variant of SLC22A1 (rs72552763) was selected for this study since its allele frequency is higher in Ethiopian population as compared to other African population. [23][24][25] Furthermore, Met420del is the most studied functional variant of SLC22A1 gene for its influence on metformin pharmacokinetics though there were inconsistent reports based an extensive survey of recent literature. In addition, this variant is generally observed in combination with a rare loss of function polymorphism, Cys88Arg (rs55918055), that causes improper membrane localization of OCT1, resulting in metformin gastrointestinal intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Solute carrier family 22 member 1 ( SLC22A1 ) gene encodes the organic cation transporter 1 (OCT1), which is expressed on the sinusoidal membrane of hepatocytes. OCT1 mediates the electrogenic transport of drugs [5].…”
Section: Introductionmentioning
confidence: 99%
“…The human SLC22A1 gene is located on chromosome 6q25.3 and encodes for organic cation transporter 1 (OCT1); it consists of 11 exons spanning 37 kb and has been shown to play an important role in the control of the glycemic response of T2DM 9. Population studies have shown a high level of polymorphisms for SLC22A1 in different ethnicities 10,11…”
Section: Introductionmentioning
confidence: 99%